COVID-19-Associated Case Fatality Rate in Subjects Under 18 Years Old in Mexico, up to December 31, 2020 - Navarro-Olivos, Efraín; Padilla-Raygoza, Nicolás; Flores-Vargas, Gilberto; Gallardo-Luna, María de Jesús; León-Verdín, Ma Guadalupe; Lara-Lona, Elia; Magos-Vázquez, Francisco J.; Díaz-Martínez, Daniel Alberto (Frontiers in Pediatrics, 2021)
Background: The emergence of the SARS-CoV-2 and the COVID-19 have become a global health crisis. The infection has been present in all the social sectors. Subjects under 18 years are one of them. The objective was to analyze the case fatality ratio of COVID-19 cases in the Mexican population under 18 years of age registered in the National Epidemiological Surveillance System from March 2020 to December 31, 2020. Material and Methods: The design is cross-sectional, quantitative, and analytical. All the suspected cases of respiratory viral disease, with a real-time polymerase chain reaction (RT-PCR) test result, aged from 0 to 17 years, were included. Descriptive statistics are presented for all the variables. Epidemiological curves were designed. The chi-squared test and its P-values were obtained to show the relationship between comorbidities and death. The case fatality ratio was computed for each comorbidity, sex, and age group. Multivariable logistic regression models were fitted to study the effect between comorbidities with the fatality of cases, adjusting for sex and age group as potential confounders. The alpha value was fixed to 0.05 to assess significance. Results: The number of records for this study was 167,856. Among them, 48,505 were from SARS-CoV-2-positive patients (28.90%), and 119,351 (71.10%) were negative. Of those who died, males (55.29%) (P < 0.05) and those under 2 years of age (50.35%) (P < 0.05) predominated. Unlike in older populations, from the comorbidities considered risk factors for death by COVID-19, only immunosuppression showed a statistically significant effect on the fatality of cases after adjustment by the other related variables. Sex and age group were not confounders for the models in those under 18 years old. Pneumonia, being younger than 5 years, and immunosuppression are related to death. Conclusion: The case fatality ratio in those under 18 years old is low. Special attention must be paid to those children under 5 years. The development of pneumonia is a warning indicator while treating them. On the other hand, having an open database of cases allows the researchers to analyze the impact of COVID-19 in different population sectors, which has clear benefits for public health.